(untitled) (LEGAL DIALOGICA, 2025)
This research aims to determine and analyze the qualifications of the criminal act of identity forgery in a fiduciary agreement and to determine the legal considerations of the judge in making a decision in the case of Decision No. 1097 / Pid.sus / 2019 / PN. Mks. This research was conducted with a normative legal research type that uses secondary legal materials or is a study by taking several books, journals or references related to the research. The results of this study indicate that (1) The qualifications of the criminal act of identity forgery in a fiduciary guarantee agreement are the requirements that must be met in order to be categorized as a crime. Forgery is the act of replacing a letter or document carried out by an individual or group of individuals. The act of forgery is a crime characterized by a framework of falsehood or fraud against an object. Fraud is an act carried out intentionally to deceive or manipulate others for personal or group interests. Thus in this case or case No. 1097 / Pid.Sus / 2019 / PN. Mks certainly meets the requirements as a criminal act. (2) Legal analysis of the judge’s decision in case No. 1097/Pid.Sus/2019/PN. Mks Regarding Identity Forgery in Fiduciary Guarantees is that the defendant has fulfilled the elements of Article 263 paragraph (1) of the Criminal Code and the elements of Article 36 of Law No. 42 of 1999 Concerning Fiduciary Guarantees. The recommendation of this study is that as law enforcement officers in determining the qualifications of criminal acts, they must be more careful in finding the elements of their actions, whether the action is a criminal act (criminal law) or a civil act (civil law) so as not to make a mistake in prosecution, and as the owner of the fiduciary object guarantee or in this case companies engaged in the fiduciary sector to be more detailed and careful when agreeing to provide fiduciary objects so that it does not happen again as in the case explained above. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis kualifikasi perbuatan tindak pidana pemalsuan identitas dalam perjanjian fidusia serta untuk mengetahui pertimbangan hukum hakim dalam menjatuhkan putusan pada perkara Putusan No.1097/Pid.sus/2019/PN. Mks. Penelitian ini dilakukan dengan tipe penelitian hukum normatif yang mempergunakan bahan hukum sekunder atau merupakan penelitian dengan mengambil beberapa buku, jurnal atau referensi yang berhubungan dengan penelitian. Hasil penelitian ini menunjukkan bahwa (1) Kualifikasi perbuatan tindak pidana pemalsuan identitas dalam perjajian jaminan fidusia adalah syarat-syarat yang harus dipenuhi agar dapat dikategorikan sebagai tindak pidana. Pemalsuan adalah tindakan mengganti surat atau dokumen yang dilakukan oleh seorang individu atau kelompok individu. Tindakan pemalsuan merupakan kejahatan yang ditandai dengan kerangka kepalsuan atau penipuan terhadap suatu objek. Penipuan adalah tindakan yang dilakukan dengan sengaja untuk menipu atau memanipulasi orang lain umtuk kepentingan pribadi atau kelompok. Dengan demikian dalam hal ini atau perkara No. 1097/Pid.Sus/2019/PN. Mks tentu memenuhi syarat sebagai tindak pidana. (2) Analisis hukum hakim putusan perkara No. 1097/Pid.Sus/2019/PN. Mks Tentang Pemalsuan identitas dalam Jaminan Fidusia adalah terdakwa telah memenuhi unsur Pasal 263 ayat (1) KUHP dan unsur Pasal 36 UU No. 42 Tahun 1999 Tentang Jaminan Fidusia. Rekomendasi penelitian ini adalah sebagai aparat penegak hukum dalam menentukan kualifikasi tindak kejahatan harus lebih teliti lagi dalam mencari unsur-unsur tindakannya, apakah tindakan tersebut berupa tindak pidana (hukum pidana) atau tindak perdata (hukum perdata) agar tidak salah dalam penuntutan, serta sebagai pemilik pemberi jaminan objek fidusia atau dalam hal ini perusahaan-perusahaan yang bergerak dibidang fidusia untuk lebih detail dan teliti saat menyetujui dalam memberikan objek fidusia agar tidak terjadi lagi seperti dalam kasus yang dijelaskan diatas.